Burden of cardiovascular disease across 29 countries and GPs’ decision to treat hypertension in oldest-old - Streit, Sven; Gussekloo, Jacobijn; Burman, Robert A.; Collins, Claire; Biljana Gerasimovska Kitanovska; Gintere, Sandra; Gómez Bravo, Raquel; Hoffmann, Kathryn; Iftode, Claudia; Johansen, Kasper L.; Kerse, Ngaire; Koskela, Tuomas H.; et al. (Taylor & Frnacis Online, 2018)
We previously found large variations in general practitioner (GP) hypertension treatment probability in oldest-old (>80 years) between countries. We wanted to explore whether differences in country-specific cardiovascular disease (CVD) burden and life expectancy could explain the differences.